The relationship between exclusion from school and mental health: a secondary analysis of the British Child and Adolescent Mental Health Surveys 2004 and 2007. Issue 4 (25th August 2017) - Ford, T.; Parker, C.; Salim, J.; Goodman, R.; Logan, S.; Henley, W.
Abstract : Background: Children with poor mental health often struggle at school. The relationship between childhood psychiatric disorder and exclusion from school has not been frequently studied, but both are associated with poor adult outcomes. We undertook a secondary analysis of the British Child and Adolescent Mental Health Surveys from 2004 and its follow-up in 2007 to explore the relationship between exclusion from school and psychopathology. We predicted poorer mental health among those excluded. Method: Psychopathology was measured using the Strengths and Difficulties Questionnaire, while psychiatric disorder was assessed using the Development and Well-Being Assessment and applying Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM IV) criteria. Exclusion from school and socio-demographic characteristics were reported by parents. Multi-variable regression models were used to examine the impact of individual factors on exclusion from school or psychological distress. Results: Exclusion from school was commoner among boys, secondary school pupils and those living in socio-economically deprived circumstances. Poor general health and learning disability among children and poor parental mental health were also associated with exclusion. There were consistently high levels of psychological distress among those who had experienced exclusion at baseline and follow-up. Conclusions: We detected a bi-directional association between psychological distress and exclusion. Efforts to identify and support children who struggle with school may therefore prevent both future exclusion and future psychiatric disorder.